2018
DOI: 10.1002/2017jd028110
|View full text |Cite
|
Sign up to set email alerts
|

Toward Synchronous Evaluation of Source Apportionments for Atmospheric Concentration and Deposition of Sulfate Aerosol Over East Asia

Abstract: Source apportionments for atmospheric concentration, dry deposition, and wet deposition of sulfate aerosol (SO42−) were synchronously evaluated over East Asia, a main source of anthropogenic sulfur dioxide (SO2) emissions. Estimating dry deposition was difficult owing to the difficulty of measuring deposition velocity directly; therefore, sensitivity simulations using two dry deposition schemes were conducted. Moreover, sensitivity simulations for different emission inventories, the largest uncertainty source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 62 publications
5
23
0
Order By: Relevance
“…The model showed intrusions of high SO 4 2− concentrations from the Asian continent. This result was consistent with our previous studies suggesting trans-boundary SO 4 2− air pollution [26][27][28][29][30]. The correlation between the daily values from the observations and the model are compared in the scatter plot in Figure 3a.…”
Section: Base-case Simulationsupporting
confidence: 91%
See 1 more Smart Citation
“…The model showed intrusions of high SO 4 2− concentrations from the Asian continent. This result was consistent with our previous studies suggesting trans-boundary SO 4 2− air pollution [26][27][28][29][30]. The correlation between the daily values from the observations and the model are compared in the scatter plot in Figure 3a.…”
Section: Base-case Simulationsupporting
confidence: 91%
“…The development of trace elements in emission inventories and model evaluations is required. Our approach for Japan should be applied to China given that trans-boundary SO 4 2− may have an impact over East Asia [26][27][28][29][30]. The refinement of the modeled aqueous-phase Fe-and Mn-catalyzed oxidation by O 2 over China may further improve the model performance during winter over both China and downwind regions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, for SO2, all models estimated more deposition than anthropogenic emissions in Japan. Previous studies based on source-receiver relationships in model experiments indicated the importance of volcanic sources and trans-boundary 15 air pollution for S over Japan (Kajino et al, 2011;Kuribayashi et al, 2012;Itahashi et al, 2017;Itahashi, 2018). Over North Asia (Mongolia and Russia), all models simulated more deposition than emissions; deposition was predicted to be 1.9 and 2.5 times higher than emissions over Mongolia and Russia, respectively, by model M2, which estimated the lowest total deposition.…”
Section: Total Deposition Mapping Over Asia 15mentioning
confidence: 78%
“…Note that this precipitation-adjusted approach assumes that errors associated with the modeled 10 precipitation are linearly related to errors in wet deposition amounts. This approach has been used in previous studies over the USA (Appel et al, 2011;Zhang et al, 2018) and Asia (Itahashi, 2018). In this study, wet depositions were adjusted for precipitation on a monthly time scale, and then the annual precipitation-adjusted wet deposition was calculated.…”
Section: Precipitation-adjusted Approach 25mentioning
confidence: 99%
See 1 more Smart Citation